SIFAT MAGNETIK TANAH DAN DAUN SEBAGAI INDIKATOR PENCEMARAN - Agum Gumelar Prakoso; Riski Darmasetiawan; Rahma Andini Pratiwi; Bambang Widjatmoko; Kartika Hajar Kirana; Dini Fitriani (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Rock magnetism have been conducted on the issue of pollution by vehicle to identify mineral magnetic in the soil surface and leaf samples. Samples taken at PT Perkebunan Nusantara VIII, West Bandung regency. Location of the study is divided into two zones, zone 1 is located close to the highway, and a zone 2 that is located away from the road. In this study magnetic susceptibility measured in two frequencies, low frequency, (0.46 kHz) and high frequency, (4.6 kHz). The measurement results show that the value of the leaf samples ranged, 1Ã10-821Ã10-8 m3/kg (zone 1), and 1Ã10-83Ã10-8 m3/kg (zone 2), On the surface soil samples, value from each frequency almost the same range 1200Ã10-81700Ã10-8 m3/kg (zone 1), and 2600Ã10-8 m3/kg2800Ã10-8 m3/kg (zone 2). The relative difference of and value will produce (%). The calculation result , (%) is within the range of 2% -4% (zone 1) and 1.4% -1.7% (zone 2). Based on the scheme between and (%), indicating that the zone 1 and zone 2 types of magnetic minerals is more likely as the mineral from the combustion of fossil gas. Keywords: pollution, vehicle pollution, magnetic susceptibility, magnetic grains.